A rare case of pediatric osteochondroma presenting as hemothorax - Pavai Arunachalam; Cenita J Sam; K Jothi Lakshmi; Hari Baskar Shanmugham (Wolters Kluwer Medknow Publications, 2020)
Isolated osteochondroma presenting as hemothorax is a rare entity. A 7-year-old boy presented with respiratory distress and diagnosed with hemothorax, and computed tomography showed osteochondroma and removal with resection of the rib was curative.